Pertumbuhan Optimal Bakteri Laut Pseudomonas aeruginosa LBF-1-0132 dalam Senyawa Piren - Safitriani, Safitriani; Thontowi, Ahmad; Yetti, Elvi; Suryani, Suryani; Yopi, Yopi (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTPyrene is a high molecular weight chemical compound belongs to polycyclic aromatic hydrocarbon (PAHs) group that are difficult to degrade by environment. Biodegradation techniques using indigenous marine bacteria are used to be as an effort to reduce pollutants that are carsinogenic. The objectives of this research are to screen of 18 marine bacteria isolates qualitatively by sublimation method and quantitatively by growth test and to optimize degradation activity of marine bacteria isolates by pyrene concentration and cell concentration. Identification by 16S rDNA and phylogenetic tree analysis were conducted to determine the molecular basis of bacterial identity. The result of sublimation showed that 15 isolates were positive result for pyrene degradation and classified to 3 groups. The first group consisted of 5 isolates that can produce clear zone, while the second group are 5 isolates with isolate color changes. The third group have both of activities. Growth test showed that isolate LBF-1-0132 has high potency to degrade pyrene compound. Isolate LBF-1-0132 is capable of degrading pyrene compounds optimally at concentration of 600 ppm and optimum cell concentration of 20. Based on 16S rDNA gene analysis, isolate LBF-1-0132 is Pseudomonas aeruginosa with 98% identity.Keywords :pyrene, marine bacteria, optimization, 16S rDNA identification